2003
DOI: 10.1089/153056203763317693
|View full text |Cite
|
Sign up to set email alerts
|

Use of Telemedicine in Evading Cholera Outbreak in Mahakumbh Mela, Prayag, UP, India: An Encouraging Experience

Abstract: Telemedicine (TM) services a process in which expert medical advice from afar is provided using electronic signals to transfer the medical data from one site to another. As a pilot project to assess the efficacy of TM in developing countries like India, a telemedicine center was set up at the main hospital of Mahakumbh mela--a grand religious fair, at Prayag, a city in north India. The daily reporting of the in-patient and outpatient cases at the fair revealed a surge of diarrhea cases among the pilgrims at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…12 Diarrhoeal diseases, including cholera, continue to be a risk at the gathering despite rapid monitoring and prompt public health interventions. 13 Another pilgrimage with a focus on water and religious rites is to Lourdes, France. This village in the Pyrenees attracts more than 5 million Catholics and other enthusiasts every year.…”
Section: Religious Mgsmentioning
confidence: 99%
“…12 Diarrhoeal diseases, including cholera, continue to be a risk at the gathering despite rapid monitoring and prompt public health interventions. 13 Another pilgrimage with a focus on water and religious rites is to Lourdes, France. This village in the Pyrenees attracts more than 5 million Catholics and other enthusiasts every year.…”
Section: Religious Mgsmentioning
confidence: 99%
“…Thirteen Stool samples were sent for testing of cholera to referral lab Mahatma Gandhi Medical College, Indore and found 2 cholera positive. A study in 2003 reported encouraging results from the use of telemedicine during the Fair for evading cholera epidemics [15].…”
Section: Discussionmentioning
confidence: 99%
“…No epidemics have been reported since then, although there are studies cautioning about potential epidemics in the future [20,21]. A study in 2003 reported encouraging results from the use of telemedicine during the Mela for evading cholera epidemics [22]. The surge in cases of diarrhoea during the fair was reported to a tertiary referral centre using a telemedicine service that uses electronic signals to transfer medical data from one site to the other.…”
Section: Living Conditions and Disease Risks Identifiedmentioning
confidence: 99%